1913 Mich. Pub. Acts 452 - (:unkn) unknown (My University, 1913)
An Act Defining the Crime of Felonious Assault and Prescribing Punishment Therefor, § 1: Whoever shall assault another with a gun, revolver, pistol, knife, iron bar, club, brass knuckles or other dangerous weapon, but without intending to commit the crime of murder, and without intending to inflict great bodily harm less than the crime of murder, shall be deemed guilty of a felonious assault, and upon conviction shall be punished by imprisonment in the State Prison for a term not exceeding three years or by imprisonment in the county jail for a term not exceeding one year, in the discretion of the court.
Keywords: COMMITTING CRIME W/ WEAPON